DIGITAL TECHNOLOGIES OF INTERACTING WITH CUSTOMERS AFTER THE PURCHASE: MAJOR TENDENCIES AND SUCCESSFUL EXPERIENCE - G. Butkovskaya (Вестник университета, 2019)
Digital transformation affects the way companies interact with clients, which is reflected in after-purchase offers. This innovation and additional use of digital technologies allow the companies to gather more data on their clients through different sources, and having the digital means of turning this data into insights and knowledge, companies can offer better products and personalized experience. The recommendations for optimizing by companies their offers at the stage after purchase to interact with the client with the help of digital technologies have been provided.